Floral scents learned inside the honeybee hive have a long-lasting effect on recruitment - Balbuena, María Sol (2012)
Floral scents learned during the waggle dance, a signal through which honeybees provide nestmateswith spatial information on foraging sites, are an important component of recruitment. Forager bees canbe reactivated to go to previously exploited food sources by perceiving scents they learned at the flowerswithin the dance context. Here, we tested whether floral scents experienced not at the foraging site, butvia scented nectar inside the nest, can influence subsequent recruitment. We determined that bees thatwere exposed to scented food while in the hive tended to follow dances in which the recruiting beepresented the same odour experienced 8 days earlier. Moreover, a higher proportion of bees with in-hiveexperience were successfully recruited to the feeding sites scented with the experienced odours than tothe feeding sites scented with novel odours. This bias in recruitment was independent of the time thatthe bees spent following dances. These findings suggest that associative memories acquired even as earlyas the first week of adult life were responsible for a variation in recruitment. We discuss our results interms of the adaptive value of the long-term olfactory memories acquired inside the nest as a facilitatorto decode the spatial information transmitted in the honeybee dance.